Advanced Foreign Experiences In Training Service Dogs And Their Significance (Eurasian Journal of Learning and Academic Teaching, 2025)
This article analyzes and examines the training of service dogs in the field of cynology in law enforcement agencies of the Republic of Uzbekistan, as well as advanced world experience. It also highlights scientific proposals and practical recommendations in the field of cynology